An Analysis Of Efficient Use Of Modifying Additives In Restoration Of Agricultural Machinery - Saychuk O.V., Kolpachenko N.M., Martynenko O.D., Honcharenko O.O. (International Journal of Advanced Science and Technology, 2020)
This studies have been carried out to evaluate the effectiveness of the method of modifying the process of recovering steel parts by surfacing to increase wear resistance. The modification involves improving the quality of the restored layer and the transition zone. The search for technological methods for introducing the additive showed that such quality requirements can be ensured by its metered introduction into the liquid bath. It was found that the optimum is the additive carbon-containing micro-diamond phase 5 – 7% of the proportion of wire. The possibility of using (nano- and micro) natural carbon-containing component as shungite and secondary raw materials as a modifier is comparatively evaluated.